Disiplin Kerja, Pengalaman Kerja Terhadap Kepuasan Kerja dan Kinerja Pengawas - Sabirin Sabirin; Ilham Ilham (JURNAL ILMIAH MANAJEMEN & BISNIS, 2020)
This research aims to determine the direct and indirect influence of work discipline and work experience on job satisfaction and supervisor performance in the Education office of South Sulawesi Province. The research used is explanative with survey approach Sampling technique with simple random sampling method. The method used in this study is to use the Partial Least Square (PLS) method. From the results of the study to the direct influence shows work discipline does not affect job satisfaction, work discipline has a positive and significant effect on performance, work experience has a positive and significant effect on job satisfaction, work experience has no direct effect on performance, further influence of work discipline negatively and significantly affects performance through job satisfaction, and work experience has a positive and significant effect on performance through job satisfaction.